2021
DOI: 10.1002/mdc3.13161
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Parkinson's Disease in the Elderly

Abstract: BackgroundBackground: Deep Brain Stimulation (DBS) is an increasingly popular therapy for Parkinson's Disease (PD). Despite the experience gained over time with DBS of either the subthalamus or the globus pallidus pars interna, there is still no consensus regarding the age limit for DBS indication. Objectives Objectives: This narrative review of the literature discusses the issues of age and DBS, emphasizing the critical need for good quality evidence to support the surgical management of elderly patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…GPi DBS has been considered the target of choice for patients with PD with frailty, including axial issues. 23 There are only four reported cases of GPi DBS in MSA. [7][8][9]19 A very recent study of 12 patients with MSA undergoing DBS (9 STN and 3 GPi) reported transient improvement of at least one symptom, although 7 had overall worsening while undergoing GPi stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPi DBS has been considered the target of choice for patients with PD with frailty, including axial issues. 23 There are only four reported cases of GPi DBS in MSA. [7][8][9]19 A very recent study of 12 patients with MSA undergoing DBS (9 STN and 3 GPi) reported transient improvement of at least one symptom, although 7 had overall worsening while undergoing GPi stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…GPi DBS has been considered the target of choice for patients with PD with frailty, including axial issues 23 . There are only four reported cases of GPi DBS in MSA 7‐9,19 .…”
Section: Discussionmentioning
confidence: 99%
“…The same applies to clinical trial limits; some studies considered 75 years old as the cutoff [ 8 , 10 ], others considered 80 years [ 11 ], and others had no specified maximum age [ 1 , 2 , 4 ]. In recent years, although there have been reports of DBS in PD patients over 70 years old [ 12 ], even in those aged 75 years and over [ 13 , 14 ], there are still relatively few such reports. With age, many brain functions decline, including working and episodic memory, cognitive and emotional function, decision making, and executive function [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…All patients voluntarily participated in this study and signed an informed consent form. For the inclusion and exclusion criteria for surgery, we referred to the previous literature [ 13 , 27 , 28 , 29 , 30 ]. The following inclusion criteria were used for eligible participants: (1) a 4 year diagnosis of idiopathic PD [ 28 ]; (2) a levodopa/apomorphine challenge test demonstrating >30% improvement in UPDRS-III score [ 29 ]; (3) motor fluctuations and/or severe dyskinesia; (4) QoL and social functioning influenced by levodopa-responsive signs; (5) clinical manifestations in off periods (unpredictable off periods, severe off periods (pain, dystonia, or panic attack), and off time more than 25% in the daytime) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation